ANALISIS YURIDIS TERHADAP SURAT KETERANGAN JUAL BELI TANAH YANG DIKETAHUI OLEH KEUCHIK GAMPONG SEBAGAI ALAS HAK DALAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) PADA KANTOR PERTANAHAN KABUPATEN ACEH TIMUR. - ZAINAL ABIDIN (jurnal.unprimdn.ac.id, 2021)
Land registration is regulated in Government Regulation Number 24 of 1997 concerning Land Registration. The authority of a keuchik in witnesses to land that is not yet certified is indeed guaranteed by the Law, but the Law which starts from the national to the regional level does not discuss in detail the authority of a keuchik. The land registration system in Indonesia uses the Torrens system. where the evidence produced is in the form of a Land Book and Certificates. The certificate as the final result of the process of registering land rights is only a strong evidence according to the provisions of the BAL, Government Regulation Number 10 of 1961 and Government Regulation Number 24 of 1997. The authority of the Keuchik in making a Purchase Certificate of land that has not been registered to obtain a certificate at the Office Land where the land is located. The status of the sale and purchase certificate of land known to the keuchik as the basis for the rights in complete systematic land registration at the National Land Office of East Aceh Regency is not clearly regulated but if it is reviewed from Government Regulation Number 24 of 1997 concerning Land Registration is regulated in Article 7, Article 8 and Article 39 The aim is to facilitate the administration of the management of buying and selling land in Kantar Land.